(3OQI GdCfaGS aj GdCOH hGdehGYX ddfGSs - (3YHO Gddg Hf MSjf GdcGQj, CHh Ydjs
(3ChdgG (B:s
(3CMeO Gddg JYGdi MeOkG cKjQoG eJhGdjoG hCUdj Ydi QShdg KGfjkG UdGI JSJZQb eY SjO GdHTQ s
(3BNQgG (B:s
(3Gddge GMTQfG hGMTQge eY GdfHjjf hGdUOjbjjf hGdTgOGA hGdUGdMjf MSf ChdFc QajbG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbj (B- (3HZOGO (B(2594) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs